Adoption of autonomous shuttle buses A qualitative study of potential adopters in Sweden - Sällberg, Erik; Hallén, David (My University, 2018)
A new industry for AVs (small autonomous shuttle buses) is emerging in Sweden, partially through an initiative that is driven by RISE (Research Institutes of Sweden). With only a few cases of adoption of AVs worldwide, the technology is still in an early phase and there is still no common understanding of what factors are influencing whether an eventual adopter will adopt the technology. Through eleven in-depth interviews with organizations that are about to adopt the AVs, the study aims to answer what factors adopters themselves perceive to be influencing their eventual adoption. In addition to the interviews, data has been gathered through participation in four workshops together with adopters and public authorities that were organized by RISE. The areas of factors are labeled as Perception of the Innovation, Collective Adoption, Facilitation by Demonstration Projects, Barriers in the Environment, and the Length of adoption process. These factors have different influence on the outcome of adoption, the rate of adoption, or the speed of adoption. This framework provides a useful structure for any actor that is aiming to diffuse AVs, including vehicle manufacturers and public transport operators.
Keywords: Innovation och entreprenörskap (nyttiggörande); Övrig annan teknik; Innovation & Entrepreneurship; Other Engineering and Technologies not elsewhere specified